Postinfectious Irritable Bowel Syndrome After Campylobacter Infection. (October 2019) - Scallan Walter, Elaine J.; Crim, Stacy M.; Bruce, Beau B.; Griffin, Patricia M.
Abstract : OBJECTIVES: Postinfectious irritable bowel syndrome (PI-IBS) is an important sequela of Campylobacter infection. Our goal is to estimate the incidence of Campylobacter -associated PI-IBS in the United States. METHODS: Data from January 1, 2010 to December 31, 2014, were obtained from the MarketScan Research Commercial Claims and Encounters Database. We identified patients with an encounter that included an International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code for "intestinal infection due to Campylobacter " (008.43) and individually matched them (on age group, sex, and length of enrollment) to a group of persons without a diagnosed Campylobacter infection (non-cases). The primary outcome of interest was a new diagnosis of IBS ( International Classification of Diseases, Ninth Revision, Clinical Modification 564.1). RESULTS: Our final matched cohort included 4, 143 cases and 20, 491 non-cases. At 1 year, the incidence rate of IBS was 33.1 and 5.9 per 1, 000 among cases and non-cases, respectively, with an unadjusted risk ratio of 5.6 (95% confidence interval [CI]: 4.3–7.3). After adjusting for healthcare utilization, the Cox proportional hazard ratio was 4.6 (95% CI: 3.5–6.1). Excluding those who received an IBS diagnosis within 90 days, the 1-year incidence rate of IBS was 16.7 and 3.9 per 1, 000 among cases and non-cases, respectively, with an unadjusted risk ratio of 4.3 (95% CI: 3.0–6.2). DISCUSSION: Persons with a Campylobacter infection have a much higher risk of developing IBS compared with those not diagnosed with Campylobacter infection. The burden of Campylobacter -associated PI-IBS should be considered when assessing the overall impact of Campylobacter infections.